2015
DOI: 10.1080/19425120.2015.1024358
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Slotted Water Control Structures on Nekton Movement within Salt Marshes

Abstract: Water control structures (WCSs) restrict hydrological connectivity in salt marshes and thereby impede nekton movement within the greater habitat mosaic. Transient fishery species, which spawn outside salt marshes and must get past these barriers to reach spawning areas or salt‐marsh nurseries, are especially vulnerable to these structures. Water control structures incorporating slots (narrow vertical openings spanning most of the water column) are thought to improve nekton passage; however, few studies have di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 55 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Reis-Filho et al (2011) found in their research that the number of species, the number of fish, and the richness and diversity of fish were significantly higher in the full moon than those in ebb tides. Kang and King (2013), Kimball et al (2015), and Paperno et al (2018) mentioned that fish found in lakes that were directly related to the sea would experience different movements according to place and time.…”
Section: Effect Of Tides On Fish Abundance and Distributionmentioning
confidence: 99%
“…Reis-Filho et al (2011) found in their research that the number of species, the number of fish, and the richness and diversity of fish were significantly higher in the full moon than those in ebb tides. Kang and King (2013), Kimball et al (2015), and Paperno et al (2018) mentioned that fish found in lakes that were directly related to the sea would experience different movements according to place and time.…”
Section: Effect Of Tides On Fish Abundance and Distributionmentioning
confidence: 99%